An Analysis of Parenting Styles on Early Childhood’s Independent Character Development - Hidayat, Yusuf; Tania, Nia; Nurhayati, Nurhayati; Kurniasih, Neng; Nuraeni, Heni; Ningsih, Sri (International Journal Corner of Educational Research, 2023)
Parenting is the interaction process between parents and early childhood to instill and develop early childhood’s characters through natural since early age. The present study aims to analyze parenting styles applied by the parents to develop the early childhood’s independent character. In addition, this study employed a case study at which the reseachers gathered the data through observation and interview towards 13 early childhoods and 13 mother (parents) as the respondents. The results of the study revealed that 61,54% of the respondents apply positive parenting style to develop their early childhood’s independent character, 23,08% of the respondents apply permissive parenting style to develop their early childhood’s independent character, and 15,38% of the respondents apply mixed parenting style (positive and permissive parenting styles) to develop their early childhood’s independent character. Thus, the majority of the respondents apply positive parenting style to develop the early childhood’s independent character at home. In conclusion, the 3 parenting styles can be collaborated each other by the parents based on the characteristics of the early childhood, the tasks given, and also the situation.